2020
DOI: 10.3390/ijms21072287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of POR*28 Polymorphisms on CYP3A5*3-Associated Variations in Tacrolimus Blood Levels at an Early Stage after Liver Transplantation

Abstract: It is well known that the CYP3A5*3 polymorphism is an important marker that correlates with the tacrolimus dose requirement after organ transplantation. Recently, it has been revealed that the POR*28 polymorphism affects the pharmacokinetics of tacrolimus in renal transplant patients. In this study, we examined whether POR*28 as well as CYP3A5*3 polymorphism in Japanese recipients and donors would be another biomarker for the variation of tacrolimus blood levels in the recipients during the first month after l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…It is reported that the influence of CYP3A5 is greater than that of CYP3A4 on the metabolism of tacrolimus [ 18 , 19 , 20 ]. However, in the CYP3A5 genotype, the efficacy of tacrolimus is affected and, therefore, a dose adjustment based on this genotype is required after organ transplantation [ 21 , 22 , 23 ]. Therefore, in the treatment of UC, the pharmacokinetics and effects of tacrolimus may be altered in the CYP3A5 genotype [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the influence of CYP3A5 is greater than that of CYP3A4 on the metabolism of tacrolimus [ 18 , 19 , 20 ]. However, in the CYP3A5 genotype, the efficacy of tacrolimus is affected and, therefore, a dose adjustment based on this genotype is required after organ transplantation [ 21 , 22 , 23 ]. Therefore, in the treatment of UC, the pharmacokinetics and effects of tacrolimus may be altered in the CYP3A5 genotype [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The T allele of the POR gene (rs1057868) is associated with increased CYP3A5 activity (16,17). Justifying that, patients carrying the T allele of the POR gene (expressers) have higher enzyme activity, low tacrolimus concentrations and high doses of immunosuppressants (17)(18)(19), favoring the development of infections.…”
Section: Discussionmentioning
confidence: 99%
“…For example, singlenucleotide polymorphisms in the gene CYP3A5 in liver transplant (LT) recipients and donors affect tacrolimus PK; in particular, donor genotype at CYP3A5 influences prognosis soon after liver transplantation. [4][5][6][7][8][9][10] The CYP3A5*1 encodes a functional cytochrome P450 enzyme, which can metabolize tacrolimus and reduce its bioavailability, whereas the CYP3A5*3 allele contains premature termination codons that give rise to truncated, nonfunctional enzyme. 4,11,12 For the same tacrolimus dose, individuals with a CYP3A5*3*3 genotype show a higher drug concentration in the blood than individuals with genotypes *1*1 or *1*3.…”
Section: Introductionmentioning
confidence: 99%